Shelf life determination of Khushmanda Rasayana towards scientific evidence for the chemical stability - Syeda Alisha Md. Isha Ali, Niharika Gaddam, Badamane Sathyanarayana Muddukrishna, Krishnamurthy Bhat, Sandeep Datarkar, Murlidhar Ballal, Surenehalli Gowdra Vasantharaju (Journal of Applied Pharmaceutical Science, 2024)
Shelf life determination of herbal formulations based on a piece of scientific evidence for a mentioned period and storage conditions defined on the container label becomes paramount for quality. This work is aimed at evaluating the shelf life of Khushmanda Rasayana by reverse phase high-performance liquid chromatography. International Council for Harmonisation storage conditions at specific time points were used to determine the marker content in the formulation. Stability studies were conducted at accelerated conditions and long-term conditions at time points (0, 1, 3, 6, 9, and 12 months). The two primary molecular markers used for developing Khushmanda Rasayana’s chemical fingerprint were Catechin and Piperine. Various quality control parameters such as appearance, thin layer chromatography, limit of detection, total ash, acid insoluble ash, alcohol soluble extractive, water soluble extractive, pH, and assay were observed by the Ayurvedic Pharmacopoeia of India. Analysis of the chemical markers over the prescribed period revealed a shelf life of 48.1 months considering the markers Catechin and Piperine. The shelf life estimated indicates the relative stability; this research expands the scope to conduct commercial stability studies in the future.
Keywords: Stability studies, shelf-life, Catechin, Piperine, Khushmanda Rasayana